The Relationship Between Hearing Loss and Cognitive Impairment in a Chinese Elderly Population: The Baseline Analysis - Fu, Xinxing; Liu, Bo; Wang, Shuo; Eikelboom, Robert H.; Jayakody, Dona M. P. (Frontiers in Neuroscience, 2021)
Objectives: To investigate the association between untreated age-related hearing loss and cognitive impairment in Mandarin-speaking older adults living in China. Methods: 293 older adults (111 males, M=70.33±4.90 years; 182 females, M=69.02±4.08 years) were recruited. All participants completed a pure tone audiometric hearing assessment, Hearing Impairment-Montreal Cognitive Assessment Test (HI-MoCA), and a computerized neuropsychology test battery (CANTAB). The Mandarin version of the De Jong Gierveld Loneliness Scale was used to measure the loneliness and the Mandarin version of the 21-item Depression Anxiety Stress Scale (DASS-21) was used to measure the current severity of a range of symptoms common to depression, stress, and anxiety of the participants. Results: A multiple stepwise regression analysis showed that the average of four mid-frequency thresholds in the better ear was related to CANTAB Paired Associates Learning (β= 0.20, p= 0.002), and the global cognitive function score (HI-MoCA), (β= -0.25, p<0.001). The average of three high frequencies in the better ear was significantly associated with CANTAB Delayed Matching to Sample (β= -0.16, p= 0.008), and Spatial Working Memory (β= 0.17, p= 0.003). Conclusion: The results revealed a significant relationship between age-related hearing loss and cognitive impairment in Mandarin-speaking older adults. These research outcomes have clinical implications specifically for hearing health care professionals in China and other populations that speak a tonal language, especially when providing hearing rehabilitation.